THE EFFECT OF FACEBOOK AND TWITTER SOCIAL MEDIA ON POLITICAL PARTICIPATION OF THE MILLENNIAL MOSLEM GENERATION - Miawati; Endang Rochmiatun; Kiki Mikail (CV. Era Digital Nusantara, 2022)
This study aims to determine the effect of social media Facebook and Twitter on the political participation of the millennial Muslim generation. The population used in this study were students of the adab and humanities faculty of UIN Raden Fatah Palembang. The sampling technique used is purposive sampling, which is taking samples with certain considerations with a total sample of 81 respondents. The type of data used is primary data and the data analysis techniques used in this research are classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the influence of social media on political participation does not have a positive and significant effect on the political participation of the millennial Muslim generation. And partially Twitter influences the political participation of the millennial Muslim generation. The value of the coefficient of determination R Square shows a value of 0.233 or 23.3% . This value shows the influence of social media on Facebook and Twitter can be explained by the variables social media, Facebook, and Twitter by 23.3% . While the remaining 76.6% is influenced by other variables that are not explained in this study. If the value of R square has a value > 0.4 to 1, then it means that it has a strong influence. 6% is influenced by other variables that are not explained in this study. If the value of R square has a value > 0.4 to 1, then it means that it has a strong influence. 6% is influenced by other variables that are not explained in this study. If the value of R square has a value > 0.4 to 1, then it means that it has a strong influence.